Analysis of the Influence of Leadership Style, Motivation, and Work Environment on Embroidery Business Productivity - Masitoh, Noneng; Badriatin, Tine; Saepudin, Asep (Almana : Jurnal Manajemen dan Bisnis, 2023)
The background to this research is that so far the work environment at the border company in Kawalu Tasikmalaya has not met the standards, because there are still rooms that lack lighting, and employee safety has not been paid attention to when cutting cloth they do not use masks. In addition to leadership and motivational factors that affect the productivity of the embroidery business, there are also environmental factors. The specific objective of this study is to apply an effective human resource management model in dealing with increasingly fierce business competition. Using the quantitative method using SPSS, 22 populations in this study were obtained based on data from the Tasikmalaya City Trade Industry (INDAG) regarding embroidery convection companies in Kawalu District, Tasikmalaya City, namely 401 registered entrepreneurs. The sampling technique used is Simple Random Sampling (SRS) so the minimum sample calculation results are 51 respondents. It can be concluded that the entrepreneurial leadership style of an embroidery company in Kawalu District is categorized as a democratic leadership style that is oriented towards relationships and results. oriented. The work environment at an embroidery company in the Kawalu sub-district is quite representative. Then the results of hypothesis testing show that leadership style, motivation, and work environment have a significant effect on work productivity.